Trends in Outpatient Primary Total Hip and Knee Replacement From the Hospital Outpatient Department and Ambulatory Surgery Center Settings in New York State - Nikhil Ailaney, MD; Derek T. Schloemann, MD; Sarah J. Wegman, BS; Jonathan Umelo, MD; Caroline P. Thirukumaran, MBBS, MHA, PhD; Benjamin F. Ricciardi, MD (Arthroplasty Today, 2025)
Background: While ambulatory surgery centers (ASCs) are increasingly used for outpatient total hip replacement and total knee replacement, collectively total joint replacement (TJR), due to association with similar or lower rates of postsurgical complications, readmissions, and reduced cost, ASC utilization trends have not been well studied. The purpose of this study was to analyze patients undergoing inpatient and outpatient TJR in New York State to identify 1) temporal site-of-service trends for inpatient and outpatient TJR and 2) characteristics of patients undergoing outpatient TJR in hospital outpatient departments (HOPDs) and ASC versus inpatient. Methods: New York Statewide Planning and Research Cooperative System database was used to identify TJR patients in each procedure setting (hospital inpatient department, HOPD, and ASC) from 2011 to 2021. We report outpatient TJR trends from 2011 to 2021 and use a multivariable generalized linear mixed model to determine characteristics of patients who have greater odds of TJR in the HOPD or ASC setting. Results: Outpatient TJR volume substantially increased over time. TJR patients in ASC compared to hospital inpatient department were younger and privately insured and had fewer comorbidities. Older, non-Hispanic Black, Hispanic patients with more medical comorbidities and patients with Medicare, Medicaid, or workers’ compensation exhibited decreased odds of TJR in both HOPDs and ASCs. Patients residing in rural areas were more likely to undergo surgery in an ASC relative to the in-patient setting for total knee replacement only. Conclusions: Patients who are older, are non-White, have increased comorbidity burdens, or are publicly insured were less likely to undergo outpatient TJR in both the HOPD and ASC settings.